Effect of university teachers’ teaching style on EFL learners’ classroom engagement: the mediating role of self-efficacy - Wei Zhou; Qiong Liu (BMC Psychology)
Abstract Background The objective of this study is to construct a model that can predict classroom engagement by Chinese EFL learners. Grounded in self-determination theory, this study specifically investigates how university teachers’ specific teaching styles (humorous, caring, logical, creative) influence EFL learners’ classroom engagement through the mediating role of self-efficacy. Methods Through convenience sampling, this study was administered on 1,064 EFL learners across seven Chinese universities and colleges representing different tiers using validated questionnaires. And structural equation modeling was employed to test the mediating role. The hypothesized model was subsequently evaluated using structural equation modeling (SEM) to assess the path coefficients and overall predictive capability of the model. Results This research found that the cognitive-oriented teaching styles (the logical teaching style and creative teaching style), but not affective-oriented styles (the humorous teaching style and caring teaching style), could significantly predict EFL learners’ classroom engagement. Besides, students’ self-efficacy could directly predict classroom engagement and mediated the link between teaching style (the logical teaching style and creative teaching style) and classroom engagement. Conclusions This study contributes to the understanding of the differential mechanisms through which cognitive-oriented teaching styles and affective-oriented styles influence EFL learners’ classroom engagement, revealing self-efficacy as the critical mediator. These findings provide concrete references for teacher training programs to prioritize logic-based instructional scaffolding and creative thinking stimulation techniques when designing pedagogical interventions aimed at enhancing learners’ self-efficacy beliefs and engagement outcomes.